Two-sided Certification: The market for Rating Agencies - Erik R. Fasten; Dirk Hofmann (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Certifiers contribute to the sound functioning of markets by reducing a symmetric information. They, however, have been heavily criticized during the 2008-09 financial crisis. This paper investigates on which side of the market a monopolistic profit-maximizing certifier offers his service. If the seller demands a rating, the certifier announces the product quality publicly, whereas if the buyer requests a rating it remains his private information. The model shows that the certifier offers his service to sellers and buyers to maximize his own profit with a higher share from the sellers. Overall, certifiers increase welfare in specific markets. Revenue shifts due to the financial crisis are also explained.
urn:nbn:de:bvb:19-epub-13216-9
Keywords: G14; G24; L15; D82; 330; Certification; Rating Agencies; Asymmetric Information; Financial Markets; Ratingagentur; Finanzdienstleistung; Kreditwürdigkeit; Asymmetrische Information; Monopol; Lieferantenmanagement; Wohlfahrtsanalyse